2020
DOI: 10.1002/lsm.23358
|View full text |Cite
|
Sign up to set email alerts
|

Intense Pulsed Light as a Treatment for Senile Purpura: A Pilot Study

Abstract: Background and Objectives Senile purpura is a common condition characterized by recurrent ecchymoses in the elderly on the extensor surfaces of the forearms, hands, and legs. Our objective is to assess the efficacy and safety of a protocol using intense pulsed light (BBL; Sciton Inc., Palo Alto, CA) to improve the appearance of senile purpura on subjects' extensor forearms. Study Design/Materials and Methods Five subjects over 65 years of age, with ecchymotic lesions measuring over 1 cm on each forearm and fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…19 Siperstein et al conducted a study on intense pulsed light (IPL) as a treatment for SP and concluded that it is safe and effective in improving the appearance and preventing further lesions. 20 Nevertheless, the limitation of IPL in treating SP lies in its non-ablative mechanism, which may require multiple series of treatment sessions to obtain the desired effects; however, comparative studies are lacking for exact comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…19 Siperstein et al conducted a study on intense pulsed light (IPL) as a treatment for SP and concluded that it is safe and effective in improving the appearance and preventing further lesions. 20 Nevertheless, the limitation of IPL in treating SP lies in its non-ablative mechanism, which may require multiple series of treatment sessions to obtain the desired effects; however, comparative studies are lacking for exact comparisons.…”
Section: Introductionmentioning
confidence: 99%